2013
DOI: 10.1167/iovs.13-12255
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Doppler Optical Coherence Tomography of Retinal Blood Flow Following Laser Photocoagulation in Poorly Controlled Diabetic Patients

Abstract: This is the first study to use Doppler FD-OCT to quantify functional changes in retinal vascular parameters in poorly controlled PDR patients. Compared to controls, blood flow parameters in these patients were decreased at baseline, but did not decrease further following PRP, with important implications related to diabetes control, endothelial function, and therapeutic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Moreover, the clinical response to PRP was found to be affected with different confounding factors, including the degree of glycaemic control,42 which was not assessed in the current study. Lee et al 27 reported no significant difference in TRBF following PRP in a cohort of poorly controlled patients with PDR. Accordingly, the current study cannot provide conclusive results regarding the effect of PRP on retinal blood flow in patients with DR.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the clinical response to PRP was found to be affected with different confounding factors, including the degree of glycaemic control,42 which was not assessed in the current study. Lee et al 27 reported no significant difference in TRBF following PRP in a cohort of poorly controlled patients with PDR. Accordingly, the current study cannot provide conclusive results regarding the effect of PRP on retinal blood flow in patients with DR.…”
Section: Discussionmentioning
confidence: 95%
“…236 baseline, but did not decrease further after PRP. 122 Blue field entoptic simulation technique was used to assess perifoveal capillary blood flow in DR. Sinclair reported increased capillary flow velocity with decreased density of the entoptically perceived leukocytes in diabetic eyes. 223 It was later shown that increased flow in the macular microcirculation may be associated with progression of DR; 75 however, a more recent report on T1DM patients with no or minimal retinopathy did not show significant difference in macular capillary blood flow.…”
Section: Fluorescein Angiographymentioning
confidence: 99%
“…Retinal vasculature is essential for evaluating retinal conditions and also for predicting the progression of some visionthreatening retinal diseases such as diabetic retinopathy (DR), glaucoma, age-related macular degeneration (AMD), and retinal vein occlusions (RVO) [1][2][3]. Accurate in vivo measurement of retinal blood flow can be used to monitor some retinal diseases.…”
Section: Introductionmentioning
confidence: 99%